Effect of smoke-free legislation on respiratory health services use in children with asthma: a population-based open cohort study in Ontario, Canada - Teresa To; Ivy Fong; Jingqin Zhu; Rachel McGihon; Kimball Zhang; Emilie Terebessy (BMJ Open)
Objective This study will add to existing literature by examining the impact of smoke-free legislation in outdoor areas among children with asthma. We aimed to examine the effect of the 2015 Smoke-Free Ontario Act (SFOA) amendment, which prohibited smoking on patios, playgrounds and sports fields, on health services use (HSU) rates in children with asthma.Methods We conducted a population-based open cohort study using health administrative data from the province of Ontario, Canada. Each year, all Ontario residents aged 0–18 years with physician diagnosed asthma were included in the study. Annual rates of HSU (emergency department (ED) visits, hospitalisations and physician office visits) for asthma and asthma-related conditions (eg, bronchitis, allergic rhinitis, influenza and pneumonia) were calculated. Interrupted time-series analysis, accounting for seasonality, was used to estimate changes in HSU following the 2015 SFOA.Results The study population ranged from 618 957 individuals in 2010 to 498 812 in 2018. An estimated average increase in ED visits for asthma in infants aged 0–1 years of 0.42 per 100 individuals (95% CI: 0.09 to 0.75) and a 57% relative increase corresponding to the 2015 SFOA was observed. A significant decrease in ED visits for asthma-related conditions of 0.19 per 100 individuals (95% CI: −0.37 to –0.01) and a 22% relative decrease corresponding to the 2015 SFOA was observed.Conclusion Based on the observed positive effect of restricting smoking on patios, playgrounds and sports fields on respiratory morbidity in children with asthma, other jurisdictions globally should consider implementing similar smoke-free policies.